Elucidation of immunological response and its regulatory network by P-TUFT-ALT-2: a promising fusion protein vaccine for human lymphatic filariasis. Issue 5 (16th May 2018) - Paul, Rajkumar; Jaiswal, Sandeep; Mahalakshmi, Natarajan; Kaliraj, Perumal
Abstract : Human lymphatic filariasis, a mosquito-borne neglected tropical parasitic disease, needs an early development of prophylactic agents such as a vaccine for its successful elimination. Our earlier study suggested the enhanced immunological response by fusion protein (P-TUFT-ALT-2) of Tuftsin and ALT-2 in a mice model. We cultured human peripheral blood mononuclear cells (PBMCs) and treated cells with Escherichia coli -expressed ALT-2 (E-ALT-2) and P-TUFT-ALT-2. Real-time polymerase chain reaction was performed to identify the mRNA copy number of various cytokine and transcription factor genes. The recombinant vaccine candidate was also validated for humans by immunoreactivity with human sera samples of natural infection. In this study, P-TUFT-ALT-2 stimulated 12% higher PBMC proliferation in endemic normal (EN) individuals than E-ALT-2 alone. There was enhanced production of IFN γ, IL-2, IL-5 and IL-12, indicating a balanced Th1/Th2 response. However, higher expression of IL-5 and lower IL-4 validate the humoral response through an IL-5-dependent manner. Also, high level of IL-17 indicates a strong Th/Treg regulation over T-cell activation. The upregulated T-bet might have enhanced IFN-γ production, whereas GATA-3 was supposed to enhance IL-5 expression. The fusion protein also exhibited 15–16% higher reactivity with EN clinical sera, exposing the upregulation of IgG1 and IgM in natural infection. The higher reactivity of P-TUFT-ALT-2 with sera of natural infection (EN) was validated indirectly by B-cell activation through various cytokines and regulatory genes produced from different T cells. Thus, these findings endorse P-TUFT-ALT-2 as a potential vaccine candidate for human lymphatic filariasis.